The unofficial guide to getting a job at Microsoft - Smith, Rebecca (McGraw-Hill, 2000)
This text provides the reader with everything needed to know to land a job at Microsoft. It covers everything from what jobs are available to an inside look at the company's recruiting, application and interview process. It also examines Microsoft's hiring philosophy and practices, and looks at the strategies used to draw the best available people to the company and keep them there for the long term.